2012
DOI: 10.1590/s1980-57642012dn06040011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in patients with clinically isolated syndrome

Abstract: Cognitive abnormalities have been extensively studied in Multiple Sclerosis (MS). However, little is known about the cognitive involvement in patients with Clinically Isolated Syndrome (CIS).ObjectiveThis study aimed to investigate cognitive impairment in patients with CIS compared with healthy subjects.Methods18 CIS patients and 18 controls were subjected to the Wechsler memory scale, Rey Auditory Verbal Learning, Rey Complex Figure, Paced Auditory Serial Addition, Digit Span, verbal fluency, Stroop color car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Over a mean follow-up period of about 3 years, the annual PBVC values were significantly lower in CIS patients when compared to the MS cohort [93]. Neuropsychological impairment, affecting mental speed processing, episodic memory, executive functions and attention, may be present in up to 50% of patients with MS [94] and has been found to occur early in the disease course [95]. Changes of brain parenchymal fraction (BPF) have been shown to predict cognitive impairment over 2 years in patients with early MS [96].…”
Section: Clinical Correlates Of Brain Atrophymentioning
confidence: 96%
“…Over a mean follow-up period of about 3 years, the annual PBVC values were significantly lower in CIS patients when compared to the MS cohort [93]. Neuropsychological impairment, affecting mental speed processing, episodic memory, executive functions and attention, may be present in up to 50% of patients with MS [94] and has been found to occur early in the disease course [95]. Changes of brain parenchymal fraction (BPF) have been shown to predict cognitive impairment over 2 years in patients with early MS [96].…”
Section: Clinical Correlates Of Brain Atrophymentioning
confidence: 96%
“…The lower frequency of cognitive impairment in the present study compared with previous studies may be due to use of the 2010 McDonald diagnostic criteria, which allow the diagnosis of RRMS to be made earlier, possibly creating lead time bias; thus, the present population may be more in keeping with previous studies on clinically isolated syndrome, the clinical precursor to MS. McIntosh-Michaelis et al 25 noted that cognitive impairment often occurred very early in the course of MS. In a systematic review of clinically isolated syndrome and cognitive impairment, Anhoque et al 26 also found evidence of cognitive impairment; the most frequently affected domains were visuospatial skills, executive function, and processing. Similar to the present results, this study directs attention to the levels of dysfunction that may exist early in the disease course.…”
Section: Practice Pointsmentioning
confidence: 99%
“…The progressive forms of MS are linked to a more pronounced and frequent cognitive deficit compared to relapsing-remitting multiple sclerosis (RRMS) [20]. However, mental disability was also observed in the early stages of the disorder, even in clinically and radiologically isolated syndromes (RISs) [21]. The definition of early-stage MS remains intensely discussed within the literature, as definitions vary among studies.…”
Section: Epidemiological Data Explaining the Burden Of Cognitive Impa...mentioning
confidence: 99%